Sheepfarminginthe SoukAhrasregion Characteristicsandtypology - Inesse,Diab (My University, 2025)
Thisstudyaimedtocharacterizethesocio-economic,structural,zootechnical,andhealth- related dimensions of sheep farming systems in the Souk Ahras province (northeastern Algeria) through a structured field survey involving 60 sheep farmers. Theresultsrevealedthatthemajorityofrespondentsweremiddle-aged(35–60years,68.3%), and education levels were critically low, with 75% having no formal schooling and none having received professional training in agriculture or livestock management. Flocks were predominantly composed of the hardy local breed OuledDjellal (96.7%), reflecting a traditional and conservative breeding approach. Most farms operated on medium (50–150 ha, 43.3%) to large-sized landholdings (>150 ha, 35%), and flock sizes ranged mostly between 40 and 100 animals (58.3%). The averagenumber of reproductive females per flock was 32.4, andmost farms kept only 1 to2rams,indicatinglimitedbreedingstockandpotentialinbreedingrisks.Matingoccurrednaturally duringtheautumnseason,andnoreproductivetechnologies(e.g.,artificialinseminationorhormonal synchronization) were in use. Feeding strategies were based on a semi-intensive system. All farmers (100%) adjusted diets according to physiological stages, particularly pregnancy. The primary feed components were hay and pasture (100%), with nearly all farmers (98.3%) also using commercial concentrates. Wateraccesswasexclusivelyspring-based.Digestivedisorderswerethemostcommonly reported health problem (65%), followed by foot-and-mouth disease and respiratory infections. Veterinary care was widely used (95%), although none of the farmers maintained mortality records. Mortality rates reached 7–8% annually, especially during autumn. Economically, the most cited constraintswerehighproductioncosts(90%)andmarketpricefluctuations(60%).Ecologically,75% of respondents reported drought as a major threat. Despite these challenges, 60% of the farmers maintained a positive perception of their activity, and 61.7% observed moderate to good productivity improvements over the past five years. Overall, the findings point to a resilient yet vulnerable sheep production system, facing structural, technical, and climatic constraints. Enhancing farmer education, veterinary support, reproductive management,andmarketintegrationwillbecrucialtoensurelong-termsustainabilityandpreservethe genetic heritage of local breeds Cette étude visait à caractériser les dimensions socio-économiques, structurelles, zootechniques et sanitaires des systèmes d'élevage ovin dans la province de Souk Ahras (nord-est de l'Algérie) à travers une enquête de terrain structurée impliquant 60 éleveurs ovins.Lesrésultatsontrévéléquelamajoritédesrépondantsétaientd'âgemoyen(35-60ans, 68,3%)etquelesniveauxd'éducationétaientextrêmementbas,75%n'ayantaucunescolarité formelle et aucun n'ayant reçu de formation professionnelle en agriculture ou en gestion de l'élevage. Les troupeauxétaientprincipalement composésdelaracelocalerustiqueOuledDjellal (96,7%),reflétantuneapproched'élevagetraditionnelleetconservatrice.Laplupartdesfermes exploitaient des terres de taille moyenne (50-150 ha, 43,3%) à grande (>150 ha, 35%), et la taille des troupeaux variait principalement entre 40 et 100 animaux (58,3%). Lenombremoyendefemellesreproductricespartroupeauétaitde32,4,etlaplupartdes fermes ne gardaient que 1 à 2 béliers, ce qui indique un cheptel reproducteur limité et des risques potentiels de consanguinité. L'accouplement a eu lieu naturellement pendant la saison automnale et aucune technologie de reproduction (p. ex. insémination artificielle ou synchronisation hormonale) n'était utilisée. Les stratégies d'alimentation étaient basées sur un système semi-intensif. Tous les agriculteurs (100%) ont ajusté leur alimentation en fonction des stades physiologiques, en particulier de la grossesse. Les principaux composants de l'alimentation étaientlefoinetlespâturages(100%),presquetouslesagriculteurs(98,3%)utilisantégalement des concentrés commerciaux. L'accès à l'eau était exclusivement basé sur les sources. Lestroublesdigestifsétaientleproblèmedesantéleplusfréquemmentsignalé(65%), suivis de la fièvre aphteuse et des infections respiratoires. Les soins vétérinaires ont été largement utilisés (95%), bien qu'aucun des agriculteurs n'ait tenu de registres de mortalité. Les taux de mortalité atteignaient 7 à 8% par an, surtout en automne. Sur le plan économique, les contraintes les plus citées étaient les coûts de production élevés (90%) et les fluctuationsdesprixdumarché(60%).Surleplanécologique,75%desrépondantsontdéclaré que la sécheresse était une menace majeure. Malgré ces défis, 60% des agriculteurs ont maintenu une perception positive de leur activité et 61,7% ont observé des améliorations modéréesàbonnesdelaproductivitéaucoursdescinqdernièresannées.Dansl'ensemble,les résultats indiquent un système de production ovine résilient mais vulnérable, confronté à des contraintes structurelles, techniques et climatiques. L'amélioration del'éducation desagriculteurs, dusoutien vétérinaire, dela gestion dela reproductionetdel'intégrationdesmarchésseracrucialepourassurerladurabilitéàlongterme et préserver le patrimoine génétique des races locales. هدفتهذهالدراسةإلىتحديدالأبعادالاجتماعيةوالاقتصاديةوالهيكليةوتربيةالحيواناتوالصحيةلأنظمةتربيةالأغنامفيمحافظةسوقأهراس)شمالشرق الجزائر(منخلالمسحميدانيمنظمشاركفيه60مزارعاللأغنام.وكشفتالنتائج أنغالبيةالمجيبينكانوافيمنتصفالعمر60-35)سنة،68.3٪(وأنمستويات التعليمكانتمنخفضةللغاية،حيثلميحصل75٪علىتعليمرسميولميحصلأي منهمعلىتدريبمهنيفيالزراعةأوإدارةالثروةالحيوانية.كانتالقطعانتتكون أساسامنسلالةأولادجلالالريفيةالمحلية96.7)٪(،ممايعكسنهجتربيةتقليدي ومحافظ.استغلتمعظمالمزارعالأراضيمتوسطةالحجم_150-50)هكتارا،43.3٪(إلى كبيرة 150>) هكتارا ، 35٪( ، وتراوح حجم القطعان بشكل أساسي بين 40 و 100حيوان 58.3)٪.( كان متوسط عدد الإناث المتكاثرة لكل قطيع 32.4 ، واحتفظت معظمالمزارعب_1إلى2كباشفقط،ممايشيرإلىوجودقطيعتكاثرمحدودومخاطر محتملةلزواجالأقارب.تمالتزاوجبشكلطبيعيخلالموسمالخريفولميتماستخدامتقنياتالإنجاب)مثلالتلقيحالاصطناعيأوالتزامنالهرموني.(واستندتاستراتيجياتالتغذيةإلىنظامشبهمكثف.قامجميعالمزارعين100)٪(بتعديلنظامهمالغذائيوفقاللمراحلالفسيولوجية،وخاصةالحمل.كانتالمكوناتالرئيسية للنظامالغذائيهيالتبنوالمراعي100)٪(،حيثيستخدمجميعالمزارعينتقريبا)98.3٪(المركزاتالتجاريةأيضا.كانالوصولإلىالمياهيعتمدحصرياعلىالينابيع.كانتاضطراباتالجهازالهضميهيالمشكلةالصحيةالأكثرشيوعا65)٪(،تليها مرضالحمىالقلاعيةوالتهاباتالجهازالتنفسي.تماستخدامالرعايةالبيطريةعلىنطاقواسع95)٪(،علىالرغممنأنأيامنالمزارعينلميحتفظبسجلاتالوفيات.وصلتمعدلاتالوفياتمن7 إلى8٪سنويا، خاصةفيفصل الخريف.منوجهةنظر اقتصادية،كانتالقيودالأكثرذكراهيارتفاعتكاليفالإنتاج90)٪(وتقلباتأسعار السوق60)٪.(منحيثالبيئة،قال75٪منالمستطلعينأنالجفافكانتهديداكبيرا.علىالرغممنهذهالتحديات،حافظ60٪منالمزارعينعلىتصورإيجابي لنشاطهمولاحظ61.7٪تحسيناتمعتدلةإلىجيدةفيالإنتاجيةعلىمدىالسنوات الخمسالماضية.بشكلعام،تشيرالنتائجإلىوجودنظاممرنولكنهضعيفلإنتاجالأغنام،يواجهقيوداهيكليةوتقنيةومناخية.سيكونتحسينتعليمالمزارعينوالدعم البيطري وإدارة التربية وتكامل السوق أمرا بالغ الأهمية لضمان الاستدامة طويلة الأجل .والحفاظ على التراث الجيني للسلالات المحلي.